The role of developmental rate, body size, and positional behavior in the evolution of covariation and evolvability in the cranium of strepsirrhines and catarrhines. Issue 151 (February 2021) - Villamil, Catalina I.
Abstract: Recent studies on hominin craniofacial evolution have focused on phenotypic integration or covariation among traits. Covariation is thought to significantly affect evolutionary trajectories, shaping the ways in which hominins and other primates could have evolved. However, the ways in which covariation itself evolves are not well understood. This study aims to investigate the role of phylogeny, development, body size, and positional behavior in shaping the strength of covariation in strepsirrhine and catarrhine primate crania ( n = 1009, representing 11 genera). These factors may have been catalysts for change in the magnitude of covariation, and they have changed significantly during primate evolution and particularly hominin evolution. Modern humans in particular have slow developmental trajectories, large bodies, and a unique form of locomotion in the form of orthograde bipedalism. Variance of eigenvalues, mean integration, mean evolvability, and mean conditional evolvability was estimated and their relationship to the various factors described earlier was assessed using phylogenetic and nonphylogenetic analyses. Results indicate that some phylogenetic signal is present, but it is not equivalent across integration statistics or cranial regions. In particular, these results suggest that closely related species are more similar than more distantly related species in evolvability of the cranial base and integration of the face. Two divergent patterns were also identified, in which covariation and evolvability of the cranial base are linked to developmental rate, but those of the face are linked to body size. Neither locomotion nor posture appears related to covariation or evolvability of the primate cranium. These results suggest that overall low covariation observed in the hominin cranium may be a result of separate trends in different cranial regions.